الألفاظ العربية المقترضة في اللغة الإندونيسية - Yenni Patriani (UIN Fatmawati Sukarno Bengkulu, 2017)
The Assimilation of Arabic Words into Bahasa Indonesia. The Arabic language has been really popular with its beauty. The present paper, theoretically, is aimed at describing the assimilation two languages, Arabic and Bahasa Indonesia. To learn Arabic language means to learn and to master this language comprehensively in any linguistic sides. For Indonesian people, learning Arabic language is not so easy and simple process. It is because there are many different linguistic systems between Bahasa Indonesia and the Arabic language including their phoneme, word order, structure of sentence, and also their meaning. On the other hand, the linguistic assimilation of both languages has done when the process occurs naturally. In any situation, many Indonesian speakers unconsciously use and adopt the Arabic vocabularies with Indonesian speech based on its spelling and linguistic system